The International Plant Sentinel Network: a tool for Regional and National Plant Protection Organizations. (April 2016) - Barham, E.; Sharrock, S.; Lane, C.; Baker, R.
Abstract : Botanic gardens and arboreta are valuable but currently under‐utilized resources in plant health research. Within their vast collections of living plants, gardens play host to expatriate plant species from across the world. These plants offer unique opportunities to study damaging pest and pathogen threats before their introduction into a region where they would be considered invasive aliens. Through these studies, scientists can determine vital information related to these organisms, which can in turn be used to strengthen understanding, contribute to pest risk analysis activities and put in place appropriate quarantine measures or other management programmes. The International Plant Sentinel Network (IPSN) has been working for the last 3 years to provide the support and resources needed for gardens to contribute to such research. The next phase of the IPSN will be to coordinate this research; it will identify, facilitate and provide the already developed tools to contributing gardens. In this way, the IPSN will provide meaningful and valuable information to plant health experts which could help mitigate, or stop altogether, the damaging impacts of new and emerging invasive alien organisms.